Symbols and meanings in the wedding ceremony "Alek Bajawek" in the opposite Piruko district of Koto Baru: Simbol Dan Makna Dalam Upacara Perkawinan “Alek Bajawek” di Seberang Piruko Kecamatan Koto Baru - fitria sari (International Journal of Technology Vocational Education and Training, 2020)
This study aims: 1) to reconstruct the procession of the marriage ceremony "alek bajawek", 2) explain how the equipment used as a symbol is used in the marriage ceremony "alek bajawek", 3) analyze the meaning contained in the equipment used as a symbol used at the marriage ceremony "alek bajawek" in Seberang Piruko, Koto Baru District, Dharmasraya Regency. The type of research used is qualitative research. This study took 28 informants, the technique of selecting informants was done by using purposive sampling technique. This type of research is ethnographic research. The research data was collected by observation, interview and documentation study. The technique of guaranteeing the validity of the data is done by being directly involved in research, seriousness in observing and by triagulation techniques. Data analysis was performed using Spradley analysis steps and the meaning of the jawi symbol is the main requirement in conducting "alek gadang" as a food to welcome the group of bako farmers. This symbol has a meaning that contains a message, so that the community makes this a reference in behavior and can be said that the Seberang Piruko community is a civilized society.